Teaching Workplace Skills to Technical Communicators - Slattery, Darina M.; Cleary, Yvonne (Communication & Language at Work, 2013)
In this article, we introduce two programmes in Technical Communication (one distance, and one on-campus) offered by the University of Limerick. Both programmes have been running for several years, but are regularly reviewed to ensure that they remain relevant. We describe how these programmes correspond to industry needs, and how they develop core competencies of technical communicators. We outline two key types of assignment (writing and development), and explain their relevance to the workplace.